Impact of Physical, Mental, and Creative Abilities Using Competitive Educational Methods: A Study on Theater Students at the College of Fine Arts, University of Mosul - Basim, Jamal Shukri; Azez , Ahlam Dara; Hamid, Aqeel Majid (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. The research aims to identify the impact of the competitive method on developing the physical, mental, and creative abilities of the Theater Department students at the College of Fine Arts at the University of Mosul. Material and methods. The research population consisted of first-year students in the Theater Department at the College of Fine Arts for the academic year (2021-2022). The research sample was a total of 10 students. The researchers used the experimental method to address the research problem, employing a homogeneous group design with pre-and post-tests. Results. The most important results of the research were the impact of the competition method on developing the physical, mental, and creative abilities of the Theater Department students at the College of Fine Arts at the University of Mosul. Conclusions. The researchers concluded that the competitive approach successfully developed students' physical and mental abilities in the Department of Theater at the College of Fine Arts at the University of Mosul. Implementing such competitive approaches in educational programs contributes to a transformative strategy for raising students’ abilities and aligning their academic journey toward professional and personal excellence. It also nurtures their critical thinking, problem-solving, and creative expression. The researchers recommended adopting the competitive method in teaching theatrical physical fitness courses in Theater Departments at Colleges of Fine Arts.